Minimum Wages and the Health and Access to Care of Immigrants' Children - Susan L. Averett; Julie K. Smith; Yang Wang (Institute of Labor Economics (IZA), 2019)
States are increasingly resorting to raising the minimum wage to boost the earnings of those at the bottom of the income distribution. In this paper, we examine the effects of minimum wage increases on the health of the children of immigrants. Their parents are disproportionately represented in minimum wage jobs, typically have less access to health care and are a growing part of the U.S. labor force. Using a difference-in-differences identification strategy and data drawn from the National Health Interview Survey from the years 2000 - 2015, we examine whether children of low-educated immigrants experience any changes in health or access to care when the minimum wage increases.
Keywords: J15; I12; I13; I14; 330; minimum wage; immigrant children; access to care; health insurance; health